STRATEGI OPTIMALISASI PROFIL PROFESIONAL DIGITAL DAN PENGUASAAN TOOLS PERKANTORAN BERBASIS CLOUD UNTUK MENINGKATKAN DAYA SAING LULUSAN LPK KABUPATEN TANGERANG - Moch Waris Laksana Agung; Afifah Khaerani A (STAI Darul Qalam Tangerang, 2024)
The high competition in the industrial labor market of Tangerang Regency requires graduates of Vocational Training Centers (LPK) to possess adaptive digital competencies and strong online professionalism. However, many job seekers have not optimized digital professional platforms and still have limited skills in using cloud-based productivity software. This Community Service (PkM) activity aims to enhance the competitiveness of LPK graduates through intensive mentoring in digital professional profile optimization (LinkedIn) and mastery of cloud-based office tools (Google Workspace). The implementation method consisted of socialization, technical operational training, and mentoring in digital portfolio preparation. The results indicated a significant increase in participants' understanding of the digital work ecosystem and technical skills in real-time document collaboration. The final evaluation proved that 90% of participants successfully built industry-standardized professional profiles, which is expected to accelerate labor absorption in the industrial areas of Tangerang Regency.